Implementasi Animasi Pada Multimedia Interaktif - Chang, Michael; Liliana, Liliana; Rostianingsih, Silvia (Jurnal Infra, 2015)
Most people do reading activities to gain knowledge, as entertainment or a hobby for people to read. From generation to generation, reading begins to decreases. Reading becomes obsolete. Nowadays, reading a book filled with writing would be boring. Books preferably instant and interesting than a book filled with long writing and tedious. While in general almost all history books are full of writing. So this time i will make an interactive multimedia that interesting and not boring about the history of the kingdom of Majapahit.In the manufacture of interactive multimedia about the history of Majapahit i implemented several important elements in interactive multimedia ie text, images, sounds, and animations are placed and adjusted the alignment between text, images, sound, and animation. The menu also made efficiently so that it can move from one topic to another topic. The addition of some visual effects that make interactive multimedia applications about the history of Majapahit becoming more.The apllication was tested to some people to see if the interactive multimedia about the history of Majapahit interesting or not. Amounting to 75,52% people said that the interactive multimedia about the history of Majapahit is more interesting rather than the book full of writing.